The Impact of Protein Intake on Insulin-Like Growth Factor-1 (IGF-1) Levels and Its Implications for Metabolic Health and Aging Processes– a literature review - Jankowska, Marlena; Baran , Karolina; Jańczyk , Natalia; Mędrysa , Karolina; Pokrzepa , Jakub Jan; Presak , Michał; Blecharz , Gabriela; Szwech , Julia; Pograniczny , Mikołaj; Mielżyńska , Adrianna (Quality in Sport, 2025)
Introduction Insulin-Like Growth Factor-1 (IGF-1) is a key hormone involved in cellular growth, metabolism, and aging. Its levels are influenced by various factors, including dietary protein intake. While IGF-1 plays a crucial role in muscle maintenance, tissue repair, and overall metabolic function, elevated levels have been associated with an increased risk of certain diseases, including cancer and metabolic disorders. Conversely, lower IGF-1 levels have been linked to longevity and reduced aging-related diseases. In particular, concerns have been raised about whey protein’s potential impact on acne flare-ups.[1] Aim of the study The primary aim of this study is to examine the relationship between dietary protein intake and Insulin-Like Growth Factor-1 (IGF-1) levels, assessing its potential implications for metabolic health and aging. This includes examining physiological mechanisms, identifying types of protein linked to acne flare-ups, and analyzing clinical studies to better understand their impact on skin health. Materials and Methods This review is based on a literature search conducted on PubMed. The following keywords were used: acne, protein supplementation, whey protein, and Insulin-like Growth Factor 1 (IGF-1), plant-based products. Conclusions Protein supplements, particularly those containing whey protein, may contribute to acne development through hormonal mechanisms such as increased IGF-1 levels and androgen production. While not everyone will experience acne from protein supplementation, individuals with a sensitivity to dairy or those who consume excessive amounts of protein may be more likely to notice acne flare-ups. Insulin-Like Growth Factor-1 (IGF-1) plays a critical role in growth, metabolism, and aging, with its levels being significantly influenced by dietary protein intake.